Transformasi Pendidikan Karakter Islami dalam Membentuk Generasi Unggul di SMP Panglima Sudirman Surabaya - Tarik, Atika Agustina; Thobroni, Ahmad Yusam (UMSU, 2024)
SMP Panglima Sudirman as an educational institution that has students from various cultures and religions. One of the religions in the school is Muslim. So that Islamic character education that focuses on the teachings of Luqmanul Hakim, Prophet Ibrahim, and Prophet Musa becomes the object of study in the implementation of the transformation of Islamic character education in an effort to form a superior generation at SMP Panglima Sudirman. Through qualitative research to explore the application of these values in the policies of those responsible for the school curriculum and their impact on the formation of student personality. It can be seen that through the research that has been carried out, it shows that the transformation of the teachings of the Qur'an in the curriculum, especially through the story of Luqmanul Hakim, Prophet Ibrahim, and Prophet Musa is reflected in the implementation of the policies of those responsible for the curriculum at SMP Panglima Sudirman. This contributes positively to forming students who have noble morals, have strong monotheism, and high enthusiasm for learning. In addition, the role of those responsible for the curriculum who support also helps in the development of students who excel academically, morally, and spiritually.